ANATOMICAL FEATURES OF PLACENTAL VASCULAR ANASTOMOSES IN PATIENTS WITH TWIN-TO-TWIN TRANSFUSION SYNDROME - Gafurova N.O., Yusupbaev R.B. (Central Asian Journal of Medicine, 2025)
Introduction: Twin-to-twin transfusion syndrome (TTTS) is one of the most severe complications of monochorionic twin pregnancy, associated with high perinatal mortality and morbidity. The main pathophysiological mechanism of TTTS is the presence of unbalanced vascular anastomoses in the shared placenta [1,2]. Objective: To study the morphological features of placental vascular anastomoses in TTTS and evaluate their prognostic significance. Materials and Methods: A morphological analysis was performed on placentas from 40 patients with TTTS after intrauterine interventions. Results: It was found that the presence of more than 7 vascular anastomoses, especially arterio-arterial anastomoses with a diameter >2 mm, was significantly associated with severe stages of TTTS. Conclusion: The findings emphasize the need to consider the morphological characteristics of the placenta when planning treatment strategies.